Mastering mountain bike skills - Lopes, Brian; McCormack, Lee 1969- (Champaign, IL Human Kinetics, 2017)
Advance your mountain biking experience even further with Mastering Mountain Bike Skills, Third Edition. Learn from the firsthand advice and personal experiences of world champion Brian Lopes. The third edition features more high-quality photos, improved instruction, and new techniques and tips for every riding style.
Introduction Chapter 1: Choose Your Weapon Chapter 2: Become One With Your Bike Chapter 3: Control Your Speed Chapter 4: Make Great Power Chapter 5: Carve Any Corner Chapter 6: Ride Down Almost Anything Chapter 7: Ride Up Almost Everything Chapter 8: Pump Bumps for Free Speed Chapter 9: Wheelie, Manual and Hop Like a Boss Chapter 10: Might as Well Jump Chapter 11: Avoid Injuries Chapter 12: Handle Every Condition Chapter 13: Flow on Any Trail Chapter 14: Race Like a Champ Glossary
Includes index.
Keywords: Mountain biking -- Training